Exploring the Picosecond Time Domain of the Solvation Dynamics of Coumarin 153 within β-Cyclodextrins - Rodriguez, Javier (2008)
We report molecular dynamics simulation results of equilibrium and dynamical characteristics pertaining to the solvation of the dye coumarine 153 (C153) trapped within hydrophobic cavities of di- and trimethylated -cyclodextrins (CD) in aqueous solutions. We found that stable configurations of the encapsulated probe are characterized by a slanted docking, in which the plane of the C153 lies mostly parallel to one of the glucose units of the CD.  In and out  dynamical modes of the encapsulated probe present very small amplitudes. The rotational dynamics of the trapped coumarine can be casted in terms of a simple model that includes diffusive motions within a local restrictive environment coupled to the overall rotational motion of the CD. We have examined the early stages of the solvation response of the environment following a vertical excitation of the probe. Regardless of the degree of the CD methylation, the water dynamical response seems to be completed within 2-3 ps, and does not differ substantially from the one observed for non-encapsulated probes. The CD response is characterized by a single, sub-picosecond relaxation that involves intramolecular motions. We also explored dynamical modes that could account for the recently reported persistence of Stokes shifts in the nanosecond time domain. In all cases, the only sources of ultraslow dynamics that we detected were those associated to gauche-trans interconversions in primary hydroxyl chains of the CD, which do not seem to be directly connected to the electronic excitation of the probe.